Oxidative Stress Implication in Retinal Diseases—A Review - Marcella Nebbioso; Federica Franzone; Alessandro Lambiase; Vincenza Bonfiglio; Paolo Giuseppe Limoli; Marco Artico; Samanta Taurone; Enzo Maria Vingolo; Antonio Greco; Antonella Polimeni (Antioxidants, 2022)
Oxidative stress (OS) refers to an imbalance between free radicals (FRs), namely highly reactive molecules normally generated in our body by several pathways, and intrinsic antioxidant capacity. When FR levels overwhelm intrinsic antioxidant defenses, OS occurs, inducing a series of downstream chemical reactions. Both reactive oxygen species (ROS) and reactive nitrogen species (RNS) are produced by numerous chemical reactions that take place in tissues and organs and are then eliminated by antioxidant molecules. In particular, the scientific literature focuses more on ROS participation in the pathogenesis of diseases than on the role played by RNS. By its very nature, the eye is highly exposed to ultraviolet radiation (UVR), which is directly responsible for increased OS. In this review, we aimed to focus on the retinal damage caused by ROS/RNS and the related retinal pathologies. A deeper understanding of the role of oxidative and nitrosative stress in retinal damage is needed in order to develop targeted therapeutic interventions to slow these pathologies.